Relationships among the basal lineages of Noctuidae (Lepidoptera, Noctuoidea) based on eight gene regions. (16th May 2013) - Zahiri, Reza; Lafontaine, Donald; Schmidt, Christian; Holloway, Jeremy D.; Kitching, Ian J.; Mutanen, Marko; Wahlberg, Niklas
Abstract : In this study, we clarify the relationships between the basal lineages in the moth family Noctuidae using DNA sequence data from eight independent gene regions. Data matrices (6.4 kbp) are analysed using parsimony and model‐based methods (maximum likelihood and Bayesian inference). Our results support the family Noctuidae as a monophyletic group in which most subfamilies have hindwing vein M2 reduced or absent. Our phylogenetic hypothesis suggests that in the Noctuidae, the plesiomorphic condition is that in which vein M2 arises about one‐third of the way up the discocellular vein between the origins of M1 and M3, mainly parallel to M3, and is of thickness similar to vein M3. Most Noctuidae lineages possess an apomorphic (derived) condition in which hindwing vein M2 is markedly reduced or totally absent, so that the cubital vein appears to be three‐branched and these lineages are hence referred to as 'trifine'. However, Noctuidae also include a number of lineages in which vein M2 is unreduced, or only slightly reduced, and these are more problematic for morphological association with the family Noctuidae. Our results also show that the subfamily Acronictinae is not closely related to Pantheinae, but instead shows a closer association with Amphipyrinae. Among the major lineages of Noctuidae, we postulate a general trend, with numerous exceptions, in larval host plants from woody plants in the basal groups towards herb feeding in derived groups. Similarly, the major radiations of monocot‐feeding groups within the family Noctuidae are in the higher trifines. The following taxonomic changes are proposed: Thiacidinae, syn. nov., a junior synonym of Pantheinae, and Dyopsinae, stat. nov., are reinstated as a subfamily.